Exploring the interrelation of family, society, and cultural influence on international Chinese and Indian STEM doctoral students in the U.S. - Xu, Xingchen (Journal of International Students, 2025)
This study employs a phenomenological approach to investigate how familial, social, and cultural influences the academic and career decision-making of Chinese and Indian STEM doctoral students in the U.S. Through semi-structured interviews with three Chinese and three Indian students, followed by thematic analysis, the study identified five themes and ten subthemes. Findings indicate that Indian students reported strong reinforcement from familial and societal expectations to pursue careers in engineering and medicine. Whereas Chinese students did not demonstrate such strong tendencies to choose specific fields of study based on familial influences. Moreover, the acculturation process of studying abroad led to a shift in identity, particularly through the development of research autonomy and financial self-sufficiency, ultimately promoting financial and educational independence. Additionally, career decisions after graduation were influenced by social policies and family background, such as work-life balance, employment opportunities, and parents’ work backgrounds.